2009
DOI: 10.1080/10714410903132907
|View full text |Cite
|
Sign up to set email alerts
|

Tourism, Tolerance, or Hospitality? An Assessment of a Native/Non-Native, Urban/Rural Youth Exchange Program Between Fort Good Hope, NWT, and East Vancouver, BC

Abstract: Alright. I want everybody to do up your seatbelts nice and tight. Wouldn't want your body to fly too far from the wreckage. Don't want yer mamas to have to search too far and wide.'' The pilot leaned back and leered at us with a wide, gap-toothed grin. The co-pilot turned and slid a big metal lunch box filled with chips and chocolate bars down in our direction.We were crammed into a ten-seater leaving Norman Wells, aiming for Fort Good Hope: half of us in this plane, half in another just behind. Very obviously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Distinctive from other types of youth mobility, youth exchanges facilitate a period of reciprocal short or long‐term mobility and hosting of individuals/members and staff from two partner organisations. Either transnational or intranational, exchanges are usually practiced by geographically, culturally, socially, economically or otherwise distinguishable groups, and aim to offer a life‐changing educational experience that can increase understanding, knowledge and dialogue through intercultural encounter (Hern 2009). They are both producers of global citizenship (Fordham 2006), and windows onto the complex relationships between a range of collaborators that includes municipal bodies, charitable organisations and grassroots community groups, all of which can have varying intentions for what a youth exchange should achieve.…”
Section: Youth Exchange Geographiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinctive from other types of youth mobility, youth exchanges facilitate a period of reciprocal short or long‐term mobility and hosting of individuals/members and staff from two partner organisations. Either transnational or intranational, exchanges are usually practiced by geographically, culturally, socially, economically or otherwise distinguishable groups, and aim to offer a life‐changing educational experience that can increase understanding, knowledge and dialogue through intercultural encounter (Hern 2009). They are both producers of global citizenship (Fordham 2006), and windows onto the complex relationships between a range of collaborators that includes municipal bodies, charitable organisations and grassroots community groups, all of which can have varying intentions for what a youth exchange should achieve.…”
Section: Youth Exchange Geographiesmentioning
confidence: 99%
“…More recently, this focus has been extended to reveal the extent to which changes in these attitudes, beliefs and knowledges are experienced by exchange participants' friends, family, programme staff and hosts (Olberding and Olberding 2010). Importantly, as well as sites of interpersonal transformation, studies by North American scholars have shown how intra‐national exchanges between First Nation—or Native—young people and both non‐Native and other First Nation young people create lasting relationships through intercommunity exchange, and revealed the extent to which youth exchanges can engender reciprocal understanding that chips away at contemporary colonial conditions (Hern 2009; Hewitt and Lee 2012). Whilst reinforcing the notion of youth exchanges as doubly “transformative” encounters, these contributions set out the potentiality for other youth exchanges to be considered sites for young people’s participation in processes of decolonisation.…”
Section: Youth Exchange Geographiesmentioning
confidence: 99%
“…Involvement in short‐term, immersive activities, such as camps, exchanges, outward bound programs, or youth conferences, have the potential to effect positive change in the psychosocial development of adolescents (Rose‐Krasnor, 2009). There is a limited amount of research on the impact of these types of programs, although they are commonly assumed to have positive benefits for youth in general (e.g., Hern, 2009; Ruedel & McInerney, 2007). Existing studies have found that youth who participate in such intense short‐term programs do report positive benefits such as increases in self‐esteem (Grocott & Hunter, 2009), self‐efficacy (Hunter et al, 2010), emotional intelligence, identity development (Duerden, Widmer, Taniguchi, & McCoy, 2009), and self‐concept (Hindes, Thorne, Schwean, & McKeough, 2008).…”
Section: Involvement In High Intensity Experiencesmentioning
confidence: 99%